1993
DOI: 10.1093/milmed/158.7.501
|View full text |Cite
|
Sign up to set email alerts
|

Spine Injuries in Combat Troops—Panama, 1989

Abstract: Operation Just Cause was until recently the largest American combat operation since Vietnam, and remains the largest nighttime parachute operation since World War II. All 252 casualties were airlifted to San Antonio, Texas, for medical treatment. Greater than 80% sustained orthopedic injuries. Sixteen patients were admitted for injuries to the back or neck. Three of the four patients with significant fractures or fracture-dislocations were paraplegic. Two of the three patients with gunshot wounds to the back r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…Attempts have been made to systematically describe injury patterns, causes, and nature of injuries sustained by US military personal in combat. Parsons et al [21] described 16 spine injuries from Operation Just Cause in 1993. Spine injuries represented 30% of fatalities and the most significant source of longterm morbidity among those soldiers wounded.…”
Section: Discussionmentioning
confidence: 99%
“…Attempts have been made to systematically describe injury patterns, causes, and nature of injuries sustained by US military personal in combat. Parsons et al [21] described 16 spine injuries from Operation Just Cause in 1993. Spine injuries represented 30% of fatalities and the most significant source of longterm morbidity among those soldiers wounded.…”
Section: Discussionmentioning
confidence: 99%
“…Countries where the conflicts took place included Croatia (3 reports 21,36,40 ), Turkey (3 reports 2,12,22 ), Iran-Iraq (1 report 1 ), Lebanon (2 reports 13,30 ), India (1 report 6 ), and Panama (1 report 31 ). There were 782 patients collectively, the majority being male and soldiers, although some papers also identified civilians as part of their patient population.…”
Section: Military Literaturementioning
confidence: 99%
“…11 Although other investigators opine that patients with progressive or new-onset neurologic deficit with a radiologically identifiable cause like missiles, bones, haematomas should be treated with urgent decompression. The indications for surgery include persistent CSF leak, dural tear to avoid meningitis and lead intoxication 6,14,17e20 Studies performed on soldiers wounded in combat zones, where the majority of injuries are high energy, have shown surgical debridement as the most efficacious factor in preventing secondary complications 12,21 A study on 65 cases of bullet injuries reported no difference in conservative and surgical management. 22 While other study indicates surgery an option in all cases.…”
Section: Treatmentmentioning
confidence: 99%